2020
DOI: 10.30945/rcr-v22i2.3256
|View full text |Cite
|
Sign up to set email alerts
|

A Importância Do Uso Da Dose Correta Na Adubação Nitrogenada De Tifton 85

Abstract: O estudo avaliou as respostas produtivas (massa verde - MV e massa seca - MS), a taxa de acúmulo de forragem - TAF, e a capacidade de suporte - CS da pastagem perene de verão Tifton 85 submetida à restrição ou excesso de nitrogênio em relação à dose recomendada. O delineamento experimental foi o inteiramente casualizado, com três doses de N: “meia”, “correta” e “dobro” e quatro repetições em cada tratamento. Após um corte de uniformização, aplicou-se N na forma de ureia de acordo com os tratamentos, e aguardou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…Agrár. Londrina, v. 42, n. 6, suplemento 2, p. 4085-4102, 2021 responsiveness of grass, in addition to not providing increases in production, not differing from the doses considered ideal, can lead to a decrease in productivity and, consequently, economic losses to the system (Patzlaff, Zulpo, & Rossi, 2020;Castagnara et al, 2011) Therefore, the use of doses that exceed the forage response potential leads to waste of fertilizer and, consequently, economic losses to the system, in addition to potential environmental losses caused by nitrate leaching (Rambo, Silva, Argenta, & Bayer, 2004). According to Ryan et al (2011), animal nutrition is related to rational management of N for forage production, which can reduce the environmental and financial impact.…”
Section: Results E Discussionmentioning
confidence: 99%
“…Agrár. Londrina, v. 42, n. 6, suplemento 2, p. 4085-4102, 2021 responsiveness of grass, in addition to not providing increases in production, not differing from the doses considered ideal, can lead to a decrease in productivity and, consequently, economic losses to the system (Patzlaff, Zulpo, & Rossi, 2020;Castagnara et al, 2011) Therefore, the use of doses that exceed the forage response potential leads to waste of fertilizer and, consequently, economic losses to the system, in addition to potential environmental losses caused by nitrate leaching (Rambo, Silva, Argenta, & Bayer, 2004). According to Ryan et al (2011), animal nutrition is related to rational management of N for forage production, which can reduce the environmental and financial impact.…”
Section: Results E Discussionmentioning
confidence: 99%
“…Andrade et al (2018) found that hay produced from Tifton 85 fertilized with 300 kg ha -1 nitrogen and harvested within 37 days resulted in higher dry matter production. Patzlaff et al (2020) concluded that doses of approximately 400 kg ha -1 allowed greater production of green mass, dry mass, and a higher forage accumulation rate for Tifton 85, compared to doses of 200 kg ha -1 .…”
Section: Characterization Of Tifton 85 Development During the Experim...mentioning
confidence: 99%
“…Estes efeitos deletérios da ausência de adubação são mais pronunciados quanto maior a exigência nutricional do capim implantado e quanto maior a taxa de lotação do sistema. Pastos não adubados adequadamente têm redução no acúmulo de forragem (Patzlaff et al, 2020) e na capacidade de suporte a cada ano. Os sinais de degradação podem ser minimizados caso o manejo seja adequado, o que demanda redução na taxa de lotação ao longo do tempo.…”
Section: Impactos Técnico-econômicos Da Adubação De Pastagem Nos Sist...unclassified